Labour supply, wages and prices in the BOF4 quarterly model of the Finnish economy - Juha Tarkka; Alpo Willman; Chris-Marie Rasi (Bank of Finland, 1989)
This paper describes the supply of labour and the determination of wages and prices in the BOF4 model. Labour supply is modelled as a function of real wage, income and discouraged worker effects. Wages are a functi on of the unemployment rate. Besides that they respond to the deviation of actual wages from equilibrium wages dictated by nominal marginal productivity. Expected inflation and taxation are entered through the separate treatment of negotiated wages. Manufacturing is assumed to be the wage leader in the economy so that developments in other sectors are affected by the wage drift in manufacturing and are tied to manufacturing wages also in the long-run.
URN:NBN:fi:bof-201807301756
Keywords: 330